2015
DOI: 10.1080/09168451.2014.991688
|View full text |Cite
|
Sign up to set email alerts
|

The opioid system majorly contributes to preference for fat emulsions but not sucrose solutions in mice

Abstract: Rodents show a stronger preference for fat than sucrose, even if their diet is isocaloric. This implies that the preference mechanisms for fat and sucrose differ. To compare the contribution of the opioid system to the preference of fat and sucrose, we examined the effects of mu-, delta-, kappa-, and non-selective opioid receptor antagonists on the preference of sucrose and fat, assessed by a two-bottle choice test and a licking test, in mice naïve to sucrose and fat ingestion. Administration of non-selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…In addition, experiments using an opioid receptor antagonist suggest that the type of food decides mechanisms of inducing preference and acquiring reinforcement effect. 8,20,21) Our present study and Kawasaki et al have also suggested that not all test solutions with aroma necessarily show preference or reinforcement effect. 6) Although there may be a congenital preference for aroma, a study has reported that the preference for aroma is acquired.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, experiments using an opioid receptor antagonist suggest that the type of food decides mechanisms of inducing preference and acquiring reinforcement effect. 8,20,21) Our present study and Kawasaki et al have also suggested that not all test solutions with aroma necessarily show preference or reinforcement effect. 6) Although there may be a congenital preference for aroma, a study has reported that the preference for aroma is acquired.…”
Section: Discussionsupporting
confidence: 75%
“…MOR stimulation in the NAc activated various hypothalamic areas, the VTA, the substantia nigra, and the NTS [ 70 ]. In mice, administration of non-selective and mu-selective opioid receptor antagonists inhibited the preference for fat over sucrose [ 166 ]. Subcutaneous administration of the non-selective opioid receptor antagonist, naltrexone, reduced the acquisition of fat reinforcement, but not the expression of learned reinforcement [ 167 ].…”
Section: Macronutrient-based Diet Selection (What We Eat)mentioning
confidence: 99%
“… 197 , 198 . In the current search, two papers discussed the involvement of the opioid system in fat preference ( 118 , 119 ). Sakamoto et al ( 119 ) looked at the effects of nonselective opioid antagonist naltrexone and mu-selective antagonist naloxonazine on both intralipid and sucrose intake.…”
Section: Discussionmentioning
confidence: 99%
“…In the current search, two papers discussed the involvement of the opioid system in fat preference ( 118 , 119 ). Sakamoto et al ( 119 ) looked at the effects of nonselective opioid antagonist naltrexone and mu-selective antagonist naloxonazine on both intralipid and sucrose intake. While more significant results were seen in sucrose intake, both naltrexone and naloxonazine antagonists reduced intralipid intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation